Human liver class I alcohol dehydrogenase gammagamma isozyme: the sole cytosolic 3beta-hydroxysteroid dehydrogenase of iso bile acids. - Marschall, H; Oppermann, U; Svensson, S; Nordling, E; Persson, B; Höög, J; Jörnvall, H (2000)
3beta-Hydroxy (iso) bile acids are formed during enterohepatic circulation from 3alpha-hydroxy bile acids and constitute normal compounds in plasma but are virtually absent in bile. Isoursodeoxycholic acid (isoUDCA) is a major metabolite of UDCA. In a recent study it was found that after administration of isoUDCA, UDCA became the major acid in bile. Thus, epimerization of the 3beta-hydroxy to a 3alpha-hydroxy group, catalyzed by 3beta-hydroxysteroid dehydrogenases (HSD) and 3-oxo-reductases must occur. The present study aims to characterize the human liver bile acid 3beta-HSD. Human liver cytosol and recombinant alcohol dehydrogenase (ADH) betabeta and gammagamma isozymes were subjected to native polyacrylamide gel electrophoresis (PAGE) and isoelectric focusing. Activity staining with oxidized nicotinamide adenine dinucleotide (NAD(+)) or oxidized nicotinamide adenine dinucleotide phosphate (NADP(+)) as cofactors and various iso bile acids as substrates was used to screen for 3beta-HSD activity. Reaction products were identified and quantified by gas chromotography/mass spectrometry (GC/MS). Computer-assisted substrate docking of isoUDCA to the active site of a 3-dimensional model of human class I gammagamma ADH was performed. ADH gammagamma isozyme was identified as the iso bile acid 3beta-HSD present in human liver cytosol, with NAD(+) as a cofactor. Values for k(cat)/K(m) were in the rank order isodeoxycholic acid (isoDCA), isochenodeoxycholic acid (isoCDCA), isoUDCA, and isolithocholic acid (isoLCA) (0.10, 0.09, 0.08, and 0. 05 min(-1) x micromol/L(-1), respectively). IsoUDCA fits as substrate to the 3-dimensional model of the active-site of ADH gammagamma. ADH gammagamma isozyme was defined as the only bile acid 3beta-HSD in human liver cytosol. Hydroxysteroid dehydrogenases are candidates for the binding and transport of 3alpha-hydroxy bile acids. We assume that ADH gammagamma isozyme is involved in cytosolic bile acid binding and transport processes as well.